2014
DOI: 10.4172/2155-9600.1000355
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies of Polyphenol Oxidase from White Yam (Dioscorea rotundata Poir) Tuber

Abstract: Enzymatic browning is engendered by conversion of monophenols (cresolase activity) and ortho-diphenols (catecholase activity) to reactive ortho-quinones in the presence of molecular oxygen by polyphenol oxidases (PPOs). The present study ascertained the inhibition kinetics of PPO extracted from Dioscorea rotundata tuber in the presence of non-toxic sulfhydryl amino acid (L-cysteine) and appraised other connecting kinetic and thermodynamic properties of D. rotundata PPO (DR-PPO). DR-PPO was extracted and purifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…This indicates that when the heating temperature increased, PPO was inactivated at a slower rate than that of POD, hence it is more stable than POD. The E a value of the PPO for the current study was closed to that reported by Zhang & Shao (2015) for loquat fruit, but lower than E a for PPO in peaches (Toralles et al ., 2005), pineapple (Lee et al ., 2009), strawberry (Chisari et al ., 2007) and white yam (Chikezie, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that when the heating temperature increased, PPO was inactivated at a slower rate than that of POD, hence it is more stable than POD. The E a value of the PPO for the current study was closed to that reported by Zhang & Shao (2015) for loquat fruit, but lower than E a for PPO in peaches (Toralles et al ., 2005), pineapple (Lee et al ., 2009), strawberry (Chisari et al ., 2007) and white yam (Chikezie, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Enzymes like proteins are made up of many amino acids through peptide bonds. Amino acids are composed of carboxyl groups (-COOH) and amine groups (-NH 2 ) which are bound to the same C atom (also called alpha carbon) (Chikezie, 2014;Demir etal., 2012). The carboxyl group provides acidic properties and the amine group provides basic properties.…”
Section: Content Validitymentioning
confidence: 99%